CONTRASTING NARRATIVES OF RELIGIOUS CONVERSION: STUDY OF “KISAH MUALAF” VERTIZONE TV AND LOG IN HUSEIN JAFAR - Fairuz, Rifqi (UIN Raden Mas Said Surakarta, 2024)
With the increasing trend of religious mediatization, the topic of religious conversion has gained significant attention in the media, both as news content and as part of Islamic dakwah narratives in Indonesia. This narrative has been widely disseminated through new media and the internet, where religious conversion stories are frequently featured in Islamic dakwah videos that attract a large audience. This article examines the “Kisah Mualaf” segment on the Vertizone TV channel and the “Log In” program on Deddy Corbuzier’s channel. “Kisah Mualaf`” presents narratives of dramatic transformation of the converts, biblical validation, and the perceived mutual threat between Islam and Christianity, shaping a dakwah content formula that represents a new generation of convert preachers. On the other hand, “Log In”, hosted by Husein Jafar, frames religious conversion narratives through comedic gimmicks while emphasizing Indonesian pluralism, reflecting the perspectives of moderate Islamic groups. Through this study, the author explores the contrasting discourses on religious conversion as a prominent narrative within Indonesia’s digital dakwah sphere. Employing content analysis, netnography, and a review of existing literature, the author argues that two dominant religious conversion narratives have emerged among digital preachers, constituting not only a competition for audience engagement but also a contestation of discourse within Indonesia’s Islamic digital dakwah landscape.